Fabrication of entangled single-wall carbon nanotube films as nanoporous junctions for ion concentration polarization. (16th February 2015) - Kim, Bumjoo; Heo, Joonseong; Kwon, Hyukjin J.; Kim, Intae; An, Taechang; Lim, Geunbae
Abstract: Ion concentration polarization (ICP) is a distinctive electrochemical phenomenon that occurs near an ion-exchange membrane with an applied DC electric field, generating a significant concentration gradient in back and forth on the membrane. To date, however, there have been only a few attempts to introduce unconventional materials for ion transport in micro–nanofluidic systems. Here, we describe the development of a novel ICP system using an entangled single-wall carbon nanotube (SWNT) film as an ion-selective membrane instead of a Nafion membrane, for investigating the detailed relationship between electrical properties, i.e., ionic conductance through nanojunctions, and nonlinear electrokinetic behavior.